Fabrication of MMMs with improved gas separation properties using externally-functionalized MOF particles1. Issue 9 (7th March 2015) - Venna, Surendar R.; Lartey, Michael; Li, Tao; Spore, Alex; Kumar, Santosh; Nulwala, Hunaid B.; Luebke, David R.; Rosi, Nathaniel L.; Albenze, Erik
<x xml:space="preserve">Abstract</x> MOF particles are surface-functionalized to achieve an improved polymer–particle interaction in mixed matrix membranes. Compared to the neat polymer, the membranes have 3 times higher CO2 permeability with 25% improvement in CO2/N2 selectivity.